Gangrenous dermatitis of fowls - Prabhakar, T G; Dorairajan, N; Shivakumar, S; Swaminathan, T Raja; Mukopadhyay, Hira Kumar; Aruni, Wilson; Poul, W Manohar (The Indian Journal of Animal Sciences, 2012)
Samples(91) comprising heart blood, affected wings, muscles, livers and kidneys were collected from 20 cases of gangrenous dermatitis (GD). Seven isolates of S. aureus, 6 isolates of Cl. perfringens and 3 isolates of Cl. septicum were obtained as single etiological agents in pure form in 16 cases. In 4 cases concurrent infection of all the 3 pathogens was observed. The isolation of both Staphylococcus species and Clostridium species from kidneys of the affected cases of gangrenous dermatitis may be the first report. Even though all the isolates were highly sensitive to norfloxaein, chloramphenicol, gentamicin and pefloxacin, varying degrees of resistance were observed to most of the antibiotics used for sensitivity test.